2008
DOI: 10.1007/s00726-008-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of resistance exercise with or without protein ingestion on muscle hypertrophy and gene expression

Abstract: The effects of timed ingestion of high-quality protein before and after resistance exercise are not well known. In this study, young men were randomized to protein (n = 11), placebo (n = 10) and control (n = 10) groups. Muscle cross-sectional area by MRI and muscle forces were analyzed before and after 21 weeks of either heavy resistance training (RT) or control period. Muscle biopsies were taken before, and 1 and 48 h after 5 x 10 repetition leg press exercise (RE) as well as 21 weeks after RT. Protein (15 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
133
3
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 50 publications
18
133
3
9
Order By: Relevance
“…In some of the experiments within this investigation, dietary intake of the subjects was registered by dietary diaries and analyzed for overall nutritional status and daily macronutrient intake. The mean protein intake per body mass varied in younger subjects between 1.3 and 1.7 g/kg/ day Ahtiainen et al 2011;Mero et al 2013) and in middle-aged and older subjects between 0.9 and 1.3 g/kg/day (Sallinen et al 2007;Hulmi et al 2009;Ahtiainen et al 2009;Sillanpää et al 2010;Ahtiainen et al 2011;Mero et al 2013). Hence, the protein intake in the majority of these subjects were above the recommended dietary allowance (RDA) of 0.8 g/kg/day and, therefore, adequate to meet the requirements for RT-induced muscular adaptations also in older adults (Campbell and Leidy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In some of the experiments within this investigation, dietary intake of the subjects was registered by dietary diaries and analyzed for overall nutritional status and daily macronutrient intake. The mean protein intake per body mass varied in younger subjects between 1.3 and 1.7 g/kg/ day Ahtiainen et al 2011;Mero et al 2013) and in middle-aged and older subjects between 0.9 and 1.3 g/kg/day (Sallinen et al 2007;Hulmi et al 2009;Ahtiainen et al 2009;Sillanpää et al 2010;Ahtiainen et al 2011;Mero et al 2013). Hence, the protein intake in the majority of these subjects were above the recommended dietary allowance (RDA) of 0.8 g/kg/day and, therefore, adequate to meet the requirements for RT-induced muscular adaptations also in older adults (Campbell and Leidy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were recruited for the study by advertising in newspapers and through e-mail lists. A subgroup from a previous study (22) was used in the present study.…”
Section: Subjectsmentioning
confidence: 99%
“…Recovery time between the sets was 2 min. The first set started with the 75% 1RM load based on the two earlier strength tests to measure baseline strength of the subjects (22). The loads were adjusted during the course of the RE bout due to fatigue so that each subject would be able to perform 10 repetitions at each set.…”
Section: Heavy Re Protocol and Nutritional Supplementation Before Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, although several studies have analyzed the effect of whey protein supplementation on resistance training performance and outcomes [6][7][8][9], only some of them have specifically focused on resistance training individuals [10,11,3,12]. Indeed, only a few studies were focused on recreationally or well strength-trained athletes, and have reported a positive effect of whey, administered alone or combined with other nutrients, to maximize strength [13,2], lean body mass (LBM) or fat free mass (FFM) gains [2,14].…”
Section: Introductionmentioning
confidence: 99%